The politics of history textbooks in South African classroom in the era of Curriculum 2005 - S. Ndimande, Bekisizwe (Revista Linhas, 2018)
South Africa has recently celebrated twenty years of political transition from apartheid government to a democratic nation. One of the important changes in this transition was the reform of classroom curriculum, including the nature of textbook content taught in post-apartheid South African schools. This article discusses the textbook content in the era of Curriculum 2005, a national curriculum statement introduced in 1997 and subsequently revised in 2002. First, I discuss the socio-political history of education in South Africa, including the transition from apartheid to post-apartheid as a context to this analysis. Second, I describe the limitations of history textbooks content taught in post-apartheid classrooms. Using critical theory, I argue that the content of newly adopted history textbooks did not radically interrupt the long-standing misrepresentation and underrepresentation of the political histories of marginalized groups in South Africa, although some textbooks have made progress than others. Keywords: History Textbooks. South Africa. Post-Apartheid. Curriculum 2005. Critical Theory.